A Collaborative Approach to OER Policy and Guidelines Development in the Commonwealth: The Case of Botswana, Cameroon, and Sri Lanka - Abeywardena, Ishan Sudeera; Karunanayaka, Shironica P.; Nkwenti, Michael N.; Tladi, Lekopanye (International Review of Research in Open and Distributed Learning, 2018)
Access to relevant learning resources is an important aspect in ensuring inclusive and equitable quality education and lifelong learning opportunities for all as outlined in the sustainable development goal 4 (SDG4). The Commonwealth of Learning (COL) has identified the development of open educational resources (OER) as a potential answer to these challenges. A total of 29 provincial/regional OER policies and guidelines were developed in Sri Lanka, Botswana, and Cameroon closely involving 608 provincial/regional policymakers from the general education system. The innovation of this project lies in the collaborative approach adopted for OER policy/guideline development where a maximum number of policymakers at the provincial/regional level have been included in the policy development process. Key applications of the approach are mass-sensitization of policymakers, identification of champions in each province or region to drive the OER agenda forward, and the development of policies/guidelines tailored to the specific needs of a particular jurisdiction. The paper will also highlight the success factors, challenges, and the follow-up activities of the project.